Comparative study of reaction degree of mineral admixture by selective dissolution and image analysis. (1st July 2016) - Han, Fanghui; Liu, Juanhong; Yan, Peiyu
Highlights: Reaction degrees are obtained by selective dissolution and BSE image analysis. Reaction degree is overestimated at early age by selective dissolution. Reaction degree is underestimated at later age by selective dissolution. Deviation of result obtained from image at different magnifications is within 5%. Image analysis gives more reliable results than selective dissolution. Abstract: The reaction degrees of slag and fly ash in composite binder pastes were comparatively studied by selective dissolution and BSE image analysis. The reaction degree of slag or fly ash determined by selective dissolution is higher than that by image analysis at early age, but the inverse regularity is observed at later age. When the selective dissolution method is used, the reaction degrees of slag and fly ash may be overestimated at early age due to the loss of the superfine particles through the filtration and the partial dissolution of slag or fly ash, and underestimated at later age owing to the presence of cement and hydration products. The narrow reacted slag rims formed at early age cannot be accurately identified during image analysis procedure, which leads to an underestimation of the reaction degree of slag. Due to the destruction of fly ash particles during grinding or polishing process, the reaction degree of fly ash obtained by image analysis is overestimated. At later age, the small particles cannot be fully counted at low magnification and the outer part of particles cannot be calculated at high magnification, and thus high reaction degree may be obtained. BSE image analysis could give more reliable results with acceptable error than selective dissolution.